Integrated Multi‐Omic Analyses Support Distinguishing Secretory Carcinoma of the Breast from Basal‐Like Triple‐Negative Breast Cancer. Issue 5 (30th March 2018) - Jin, Min‐Sun; Lee, Hyebin; Woo, Jongmin; Choi, Seongmin; Do, Mi Sol; Kim, Kwangsoo; Song, Min Ji; Kim, Youngsoo; Park, In Ae; Han, Dohyun; Ryu, Han Suk
Abstract : Purpose: Secretory carcinoma (SC) of the breast is defined as an indolent tumor but is still categorized into a basal‐like triple‐negative breast cancer (BL‐TNBC) subgroup that generally shows aggressive behavior according to the current classification. Despite the unique clinical behavior of SC, molecular characteristics that reflect biological behaviors of SC remain largely unknown. Experimental design: A combinatorial approach of whole‐exome sequencing and mass spectrometry–based in‐depth quantitative proteomics to determine the entire molecular landscape of SC using three SC formalin‐fixed paraffin‐embedded (FFPE) tissues is employed. Results: Exome sequencing and proteomic analysis of SC identified 419 unique somatic mutations and 721 differentially expressed proteins as compared with triple‐negative breast cancer (TNBC), respectively. Several pathways related to cancer metabolism were significantly upregulated in the SC group. Comparative analyses with multiple datasets revealed that SC shares genomic mutations and biological pathways more closely related to hormone receptor–positive breast cancer than BL‐TNBC. Conclusion and clinical relevance: These multi‐omic analyses provide evidence that SC harbors substantially different molecular genomic and proteomic landscapes compared with BL‐TNBC. These results provide an entire spectrum of in‐depth molecular landscapes to support the hypothesis that SC is distinct from BL‐TNBC.